Newly described anatomical opening on forelimb tendon in the artiodactyls and its relation to knee clicks - Pyszko, Martin; Němeček, Petr; Horák, Ondřej; Páral, Václav; Kotrba, Radim; Hoffman, Louwrens C; Robovský, Jan (Scientific reports, 2022)
To understand which morphological/anatomical parts may be responsible in artiodactyl ungulates for the clicking sound made when moving, this research focuses on the forelimb tendon apparatus where an undescribed opening in the fibrous cuff (manica flexoria), called hereafter for its shape as an "oval window" in the manica flexoria (OWMF), was detected. This oval window was found in 24 of the 25 species of four families (Camelidae, Giraffidae, Cervidae, and Bovidae) evaluated; the exception being in Bos taurus taurus (Domestic cattle). The length and width of the OWMF enabled correct species discrimination between the majority of species, but remained conservative intraspecifically, as it did not differ between the left and right side of the forelimb, third and fourth digits, or between sexes. When evaluating the shape of OWMF in individual species, and measuring its length and width, 18 out of the 24 species investigated had this window as an oval shape, the remaining 25% of species exhibited more oval-oblong shapes with either proximal or distal asymmetry. The function of the OWMF in the thoracic autopodium of most ruminant even-toed ungulates is not yet fully understood. Its most likely function is to help balance the pressure inside the ligament cuff and reduce the friction of the touching surfaces of the muscle tendons-thus facilitating the movement of the digits when walking. None of the absolute or relative OWMF parameters fit exclusively with the occurrence and distribution of knee-clicks produced by some bovids and cervids during movement, so the mechanism responsible for this sound remains cryptic from the present anatomical perspective.
Keywords: Cattle; Ligaments; Animals; Tendons; skot; přední končetina; lidé; horní končetina; zvířata; Deer; Upper Extremity; ligamenta; Artiodactyla; vysoká zvěř; Forelimb; šlachy; Humans